Following the “South American model” - Vonnard, Philippe (Universidad Centro Latinoamericano de Economía Humana (Universidad CLAEH), 2021)
In June 1954, 28 national football associations from all over Europe met in Basel, Switzerland, to create a continental organization. Renamed as Union of European Football Associations (UEFA) in October 1954, in less than ten years it became a major actor in European football, a leading role which it continued to play in the decades that followed. How can the creation of this organization be explained during the Cold War, when Europeans were divided? What were the main sources of inspiration for the advocates of UEFA? From a globalized perspective, this paper addresses these two questions by focusing on the role played by South American football administrators in this process. This research is primarily based on documents from the FIFA archives, in particular the minutes of both the Executive and Emergency Committees and the Congresses, as well as mail correspondence. These documents have been cross-referenced with other archives of national associations and a careful review of L’Equipe and France Football, newspapers with international scope.